Creating Women Concept-Characters in P. Zagrebelny’s Fictional Discourse - Karpenko, Nataliia (2021)
The article focuses on the verbalisation of the concept woman in P. Zagrebelnyi’s fictional discourse. The artist is analysed, on the one side, as a linguistic personality with his features of psyche, as a representative of a language group, and on the other side, as a creative personality that uniquely represents himself in fictional discourse, creative dimensions with his features of communicative behaviour. The analysis of the concept is performed regarding the achievements of psycholinguistics, gender linguistics, lingua-cultural studies, pragmatically-oriented communicative linguistics, on the basis of anthropocentric and discoursecentric paradigms, that made it possible to identify senses in the structure of the concept and clarify the mechanism of their occurrence. Attention is paid to the writer’s fictional discourse, which is analysed with regard to principles of discourse-analysis. Therefore, extralingual factors that gave rise to certain lexemes representing the concept are crucial for the research. As a result of the study, groups of lexemes that constitute the concept and denote animals, birds, natural phenomena, pieces of land were revealed. Nouns that constitute a layer of military vocabulary and name psychological states and contain negative connotations were identified. Features characteristic of women representatives of Ukrainian culture are compared and contrasted with the descriptions of women representatives of other cultures. The language units, evoked by the mentality and mental outlook of Ukrainians, were analysed.